Solvent Extraction : Classical and Novel Approaches. - Kislik, Vladimir S, I. (Elsevier Science, 2011)
The main challenge in modern solvent extraction separation is that most techniques are mainly empirical, specific and particular for narrow fields of practice and require a large degree of experimentation. ThisÈconcise and modernÈbook provides aÈcomplete overview of both solvent extraction separation techniques andẗhe novel and unified competitive complexation/solvation theory. This novel and unified technique presented in the book provides a key forä preliminary quantitativeÈprediction ofÈsuitable extraction systemsẅithout experimentation, thus savin.